Present status of Fusarium dry rot of potato tubers in Isfahan (Iran) - ESFAHANI, M. NASR (Indian Phytopathology, 2006)
Fusarium dry rot of potato tubers was found to be the main disease in Isfahan (Feraydan) Iran. Four Fusarium spp. were isolated from dry rot lesions of potato tubers collected from 50 farms in 17 production localities. F. sulphureum and F. solani were the predominant species. Three species (F. sulphureum, F. solani and F. oxysporum) caused typical dry lesions in inoculated potato tubers, whereas F. chlamydosporum was confined to sunken or dimple-like necrotic lesions. F. sulphureum was the most aggressive species followed by F. solani and the least one, F. oxysporum. The pathogenicity tests on four potato varieties showed little correlation between the rank order of susceptibility of the potato varieties to the two main pathogens.